(untitled) (New York, 2001)
Most research in the life sciences involves a core set of molecular–based equipment and methods, for which there is no shortage of step–by–step protocols. Nonetheless, there remains an exceedingly high number of inquiries placed to commercial technical support groups, especially regarding problems. Molecular Biology Problem Solver: A Laboratory Guide asks the reader to consider crucial questions, such as: Have you selected the most appropriate research strategy? Have you identified the issues critical to your successful application of a technique? Are you familiar with the limitations of a given technique? When should common procedural rules of thumb not be applied? What strategies could you apply to resolve a problem? A unique question–based format reviews common assumptions and laboratory practices, with the aim of offering a firm understanding of how techniques and procedures work, as well as how to avoid problems.
Keywords: Molecular biology,Molecular biology; Methodology,Laboratory manuals